Promotion of Behavioral Change and the Impact on Quality of Life in Elderly Patients with Advanced Cancer: A Physical Activity Intervention of the Multimodal Nutrition and Exercise Treatment for Advanced Cancer Program - Takako Mouri; Tateaki Naito; Ayumu Morikawa; Noriatsu Tatematsu; Satoru Miura; Taro Okayama; Katsuhiro Omae; Koichi Takayama (Elsevier, 2018)
Objective: Physical activity (PA) may improve the quality of life (QOL) of cancer survivors. However, the impact on patients with advanced cancer with high cachectic potential is unknown. We analyzed the feasibility of PA intervention using the multimodal program Nutrition and Exercise Treatment for Advanced Cancer (NEXTAC) and the impact on QOL in elderly patients with advanced cancer. Methods: We recruited 30 patients aged ≥70 years who were scheduled to receive the first-line chemotherapy for newly diagnosed advanced pancreatic or non-small-cell lung cancer. The QOL was assessed using the European Organization for Research and Treatment of Cancer QOL Questionnaire version 3.0, while the PA was measured using a pedometer/accelerometer. Instructors counseled patients to increase daily activity in an 8-week educational intervention. We assessed patient attendance, compliance, and intervention efficacy. Results: The median patients' age was 75 years (range, 70-84 years). Twelve patients (40%) were cachectic at baseline. Twenty-eight (93%) patients attended all sessions. Six (21%) and 15 (52%) patients increased their indoor and outdoor activity, respectively. There were significant differences in measured PA, global QOL, and role and emotional functioning between the patients who increased outdoor activity and those who did not. Conclusions: The PA intervention of the NEXTAC program was feasible as the elderly patients with advanced cancer in this study were highly compliant. The majority of patients demonstrated behavioral changes that were associated with the improvement in global QOL. We conduct a randomized phase II study to measure the impact of the NEXTAC program on QOL and functional prognosis.